Competence and Motivation (Auditor) on Audit Quality - Mildawani, MM Tri Susetyaning (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Assessing the efficiency of financial supervision in local government is contingent upon the crucial factor of audit quality. The significance of audit quality to information consumers lies in its capacity to serve as a fundamental framework for decision-making. Numerous aspects exert influence in pursuing enhancing and attaining commendable audit quality, encompassing competence and enthusiasm. The objective of this study is to examine the impact of auditor competency and auditor motivation on the quality of audits conducted by the Cirebon Regency Inspectorate Office. The present study was conducted at the Cirebon district's Inspectorate office. The investigation utilized a sample size of 50 auditors. The purposive sampling technique chose the participants for this study. The investigation employed the analytical technique of descriptive statistics. The data underwent statistical analysis using SPSS version 25, employing multiple linear regression tests and hypothesis testing. Before doing the multiple linear regression analysis, it is customary to perform the classical assumption test, which involves assessing the validity and reliability of the data. The study's findings indicate that the level of auditor skill has a notable and favorable impact on the quality of audits. The motivation of auditors has been found to have a notable positive impact on the quality of audits.